Novel electrospun separator-electrolyte based on PVA-K2CO3-SiO2-cellulose nanofiber for application in flexible energy storage devices - Abdulkadir, B.A. (John Wiley and Sons Inc, 2022)
Electrospun fiber membrane as a separator-electrolyte have been prepared in this study using electrospinning process from cellulose acetate, PVA, K2CO3, and SiO2 with different concentrations. Five different concentration were prepared (14â22 wt) using mixture of dimethyl sulfoxide and acetone in a fixed ratio of 2:3. The prepared electrospun membranes were characterized and shown to exhibit good and well-structured morphology formed by interlaying of fibers, where the thinnest and finest fibers were achieved at 20 wt polymer concentration, resulting in average diameters of 480 Â± 80 nm. The prepared membranes were activated with plasticized gel polymer electrolyte where its electrochemical properties/performance was evaluated. Based on the good porous nature of the fiber, the membrane with 20 wt concentration exhibited good electrolyte uptake of 450.75 that is higher than the commercially prepared separator. Similarly, the membranes displayed good electrolyte retention (R) ability of 8.8. The ionic conductivity studies revealed that, the conductivity of the electrospun membranes increased with increasing polymer concentration up to 20 wt where an optimum ionic conductivity of 3.73 Ã 10â3 and 7.54 Ã 10â3Â Scmâ1 at ambient temperature and 373.15 K, respectively, have been achieved. The oxidation stability of the prepared membrane in this study showed a good electrochemical stability of up to 4.8Â V that is higher than that of the commercially prepared membrane and other reported electrolytes. Â© 2022 Wiley Periodicals LLC.